Diversity aided millimeter‐wave/free space optical cooperative relaying systems. (11th January 2021) - Goel, Amit; Upadhya, Abhijeet; Dwivedi, Vivek K.
Summary: In this paper, we investigate the performance of mixed millimeter‐wave (mmWave)/multiple input multiple output (MIMO)‐free space optics (FSO) cooperative relaying system. The mmWave link is assumed to undergo multipath fading and shadowing which has been modeled as generalized‐ K distributed fading, whereas the diversity aided FSO link is considered to experience Gamma–Gamma turbulence. We consider amplify‐and‐forward (AF) relaying strategy and multiple signals arriving at the receiver are combined using equal gain combining (EGC) scheme. Analytical closed form expressions for performance metrics such as outage probability, bit error rate (BER), and the ergodic channel capacity are derived in terms of bivariate Fox's H‐function for the considered mixed mmWave/MIMO‐FSO relaying system. In order to further simplify the obtained results, we analyze the system performance for the case of high signal‐to‐noise ratio (SNR) to present the asymptotic expressions for the outage probability and BER in terms of elementary functions. To this end, we have formulated an optimum power allocation scheme which minimizes the probability of outage experienced by the end user by allocating the optimum power on the FSO link. We also analyze the proposed system for the impact of pointing errors in a separate section by deriving closed‐form expressions for the outage probability and BER. Finally, numerical results have been demonstrated the findings of the research work which have supplemented by Monte Carlo simulations. Abstract : In this paper, the performance of mixed millimeter‐wave (mmWave)/multiple input multiple output (MIMO)‐free space optics (FSO) cooperative relaying system has been investigated. The integration of mmWave and FSO has the capability to address the high bandwidth requirements of the future wireless networks. Analytical closed‐form expressions for performance metrics such as outage probability, coding gain, diversity order, bit error rate (BER), and the ergodic channel capacity have been derived. Asymptotic high SNR approximate analysis has also been presented in the research work. Additionally, the impact of pointing errors has been quantified by presenting the expression for the outage probability and BER for the proposed model. The considered mmWave/MIMO‐FSO relaying system model is shown in figure below: